2015
DOI: 10.1088/2057-1976/1/2/025204
|View full text |Cite
|
Sign up to set email alerts
|

Fast range measurement of spot scanning proton beams using a volumetric liquid scintillator detector

Abstract: Accurate confirmation and verification of the range of spot scanning proton beams is crucial for correct dose delivery. Current methods to measure proton beam range using ionization chambers are either time-consuming or result in measurements with poor spatial resolution. The large-volume liquid scintillator detector allows real-time measurements of the entire dose profile of a spot scanning proton beam. Thus, liquid scintillator detectors are an ideal tool for measuring the proton beam range for commissioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The line profile across the acrylic phantom provided the full-width at half maximum (2.78 cm) value that is close to the physical diameter (2.8 cm) of the acrylic insert. The smooth edges of the line profiles were likely due to cone beam projection of the inserts resulting from a combination of proton beam divergence (2.12°, for a 10 cm 2 field area formed by beam source placed 270 cm away from the isocenter plane), as suggested by Tanaka et al (2016), and from camera system divergence (Hui et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The line profile across the acrylic phantom provided the full-width at half maximum (2.78 cm) value that is close to the physical diameter (2.8 cm) of the acrylic insert. The smooth edges of the line profiles were likely due to cone beam projection of the inserts resulting from a combination of proton beam divergence (2.12°, for a 10 cm 2 field area formed by beam source placed 270 cm away from the isocenter plane), as suggested by Tanaka et al (2016), and from camera system divergence (Hui et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Robertson et al used simulated three‐dimensional LET distributions and Birks’ model to correct for quenching effects in measured proton PDL curves. This correction was then used for fast measurements of the range of proton pencil beams . It relies on the accurate matching of the predicted and the measured LET distributions and is therefore prone to small shifts between the simulated and the measured Bragg curve .…”
Section: Introductionmentioning
confidence: 99%
“…This correction was then used for fast measurements of the range of proton pencil beams. 22 It relies on the accurate matching of the predicted and the measured LET distributions and is therefore prone to small shifts between the simulated and the measured Bragg curve. 1,23 Range information has also been extracted from the scintillation light output without applying any correction for quenching at all.…”
Section: Introductionmentioning
confidence: 99%
“…However, film is not efficient for a frequent constancy check of ranges for multiple proton energies because of postprocessing requirements and the number of films required. Volumetric scintillator detectors have also been used for fast range verification in proton therapy, and a few recent studies reported that sub‐millimeter accuracy was achieved, but this is not currently a commercially available technology.…”
Section: Introductionmentioning
confidence: 99%